CIVIL SERVANTS’ READINESS IN FACING THE IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE IN LOCAL GOVERNMENT BUREAUCRACY - Marzuki; Mujahidin (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
This study aims to analyze civil servants’ readiness in facing the implementation of artificial intelligence in local government bureaucracy. The study focuses on civil servants’ capacity, digital literacy, technological competence, organizational culture, and bureaucratic resistance to AI-based transformation. This research uses a qualitative method with an exploratory-descriptive approach and conceptual framework development. Data were collected from secondary and documentary sources, including recent peer-reviewed journal articles, policy documents, institutional reports, regulatory materials, and scholarly works related to AI adoption, digital transformation, civil-service competence, public-sector innovation, organizational culture, and bureaucratic resistance. The data were analyzed using thematic analysis by classifying findings into digital literacy, technological competence, organizational culture, leadership support, bureaucratic resistance, ethical awareness, and institutional support. The findings show that AI implementation in local government depends not only on technological infrastructure, but also on civil servants’ ability to operate digital systems, interpret algorithmic recommendations, evaluate data quality, and maintain public accountability. The study also finds that bureaucratic resistance may arise from fear of job displacement, loss of authority, weak technical confidence, rigid work culture, and lack of training. The main contribution of this study is the formulation of a human-centered AI readiness framework consisting of digital literacy, technological competence, adaptive organizational culture, ethical awareness, and institutional support. This framework emphasizes that civil servants are the key actors of successful AI transformation in local government bureaucracy.